Ultrastructural and molecular biologic comparison of classical proprioceptors and palisade endings in sheep extraocular muscles - RUNGALDIER, Stefanie (Invest Ophthalmol Vis Sci, 2009)
PURPOSE: To analyze and compare the structural and molecular features of classical proprioceptors like muscle spindles and Golgi tendon organs (GTOs) and putative proprioceptors (palisade endings) in sheep extraocular muscle (EOMs). METHODS: The EOMs of four sheep were analyzed. Frozen sections or whole mount preparations of the samples were immunohistochemically labeled and analyzed by confocal laser scanning microscopy. Triple labeling with different combinations of antibodies against neurofilament, synaptophysin and choline acetyltransferase (ChAT) as well as α-bungarotoxin and phalloidin was performed. Microscopic anatomy of the nerve end organs was analyzed by transmission electron microscopy. RESULTS: The microscopic anatomy demonstrated that muscle spindles and GTOs had a perineural capsule and palisade endings a connective tissue capsule. Sensory nerve terminals in muscle spindles and GTOs contained only few vesicles whereas palisade nerve terminals were full of clear vesicles. Likewise, motor terminals in the muscle spindles’ polar regions were full of clear vesicles. Immunohistochemistry showed that sensory nerve fibers as well as their sensory nerve terminals in muscle spindles and GTOs were ChAT-negative. Palisade endings were supplied by ChAT-positive nerve fibers and the palisade complexes including palisade nerve terminals were also ChAT-immunoreactive. Motor terminals in muscle spindles were ChAT and α-bungarotoxin -positive. CONCLUSIONS: The present study demonstrated in sheep EOMs that palisade endings are innervated by cholinergic axons exhibiting characteristics typical for motoneurons whereas muscle spindles (except the polar regions) and GTOs are supplied by non-cholinergic axons. These results question whether palisade endings are candidates for proprioceptors in EOMs.